dalam pementasan sebagai kajian esensi di jurusan teater STKW sSurabaya - LESTARI, LILIS (GETER : Jurnal Seni Drama, Tari dan Musik, 2024)
Supali's acting style in the play Supali gendeng Wedokan (SGW) is an original research by the author, which is an academic work to find out Supali's acting style as a creative East Javanese actor who reacts in folk theater performances such as ludruk. Ludruk has become a traditional theater that has meaning as a good learning medium in society, especially East Java. As a study, it is necessary to examine the rich acting of ludruk actors who maintain the atmosphere of ludruk art until it is owned by the interested community. Supali is not even distant from the community, the figure of Supali has become an icon in every performance he plays so that every presence in the performance is always attended by his fans, namely the community, especially East Java. The purpose of this research is to find out the extent of the development and progress of Supali's acting style as an Indonesian traditional theater actor, especially when playing roles in the SGW play. Based on the overall description that has been done in the form of analysis, the answer to the formulation of this research problem, Supali's acting style in the performance of "Supali Gendeng Wedokan" in the performance produced by Perdana Record is a representation acting that contains many elements of acting styles that can be applied in one-time performances. The author also sees that Supali does mix-acting in his application when playing a character, be it a character outside himself, or playing his own character. In terms of acting style, Supali seems to dominate the caricatural style. In some sessions, Supali's acting can also be seen as in realism theater mixed with elements of Western theater. Thanks to his cleverness in processing the acting in a stylized way, Supali's acting is able to cause an alienation effect on the audience. The performance of SGW's play then solidified Supali's characteristics as a folk theater actor, especially ludruk, which contains elements of improvisation, humor or comedy, the use of East Javanese vocabulary, scenes based on gedripan, simple staging, spontaneous acting, kinship system directing, and singing, kidung and tembang.